Remark
You should use brackets just to make sure that the x is multiplied by 2/3 and is not some like 2/(3x). Having made the assumption that that is not what you meant I'll answer this the way I have written it.
y = (2/3) * x + 4
A
x =0
y = (2/3) * 0 + 4
y = 4
B
x = 3
y = (2/3) * 3 + 4 The threes cancel out leaving you with 2 as the first number after the equal sign on the right.
y = 2 + 4
y = 6
C
x = - 9
y = (2/3)(-9) + 4
y = 2 (-3) + 4
y = - 6 + 4 Think money. If you are 6 dollars in the hole and someone give you 4 dollars you are now only 2 dollars in the whole.
y = - 2
D
y = (1/2)*(2/3 + 4 The twos cancel out
y = 1/3 + 4
y = 4 1/3 = 13/3 or 4.33333. It depends on what your marker expects.